1998
DOI: 10.1046/j.1365-2435.1998.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Economics of spider orb‐webs: the benefits of producing adhesive capture thread and of recycling silk

Abstract: Summary1. The replacement of dry, fuzzy cribellar prey capture thread by viscous, adhesive capture thread was a major event in the evolution of orb-weaving spiders. Over 95% of all orb-weaving species now produce adhesive threads. 2. Adhesive thread achieves its stickiness with a much greater material economy than does cribellar thread. 3. Transformational analyses show that, relative to spider mass, adhesive orb-weavers invest less material per mm of capture thread and produce stickier capture threads than do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 43 publications
1
98
0
8
Order By: Relevance
“…There are, for instance, two methods of creating sticky silk; cribellate spiders employ finely combed fibrils, whereas ecribellate spiders use a viscous glue‐like substance. These two methods may affect prey capture efficiency of different prey types (Opell, 1997, 1998). In fact, it has been shown that cribellate webs have improved retention of prey, which could enhance capture of larger or stronger prey types and minimize the size of a web without compromising function (Nentwig, 2013; Opell, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, for instance, two methods of creating sticky silk; cribellate spiders employ finely combed fibrils, whereas ecribellate spiders use a viscous glue‐like substance. These two methods may affect prey capture efficiency of different prey types (Opell, 1997, 1998). In fact, it has been shown that cribellate webs have improved retention of prey, which could enhance capture of larger or stronger prey types and minimize the size of a web without compromising function (Nentwig, 2013; Opell, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, spiders invest different amounts of silk when building a functional web, with tangle < orb <<< sheet‐tangle (ALG, unpublished data). Overall, estimations of the amount of N required to build and maintain a functional web is complex due to either the chemical properties of the silk itself, differences in the quantities required to construct their webs, or due to the silk recycling through silk ingestion processes, as orb weavers do (Opell, 1998). Further research into the nutrient budgets associated with silk production and energetic web investment in tangle and other types of spider webs may be a key to understanding the nutritional and energetic requirements in spiders, and determining whether C, N, or P supply from their prey may be limiting for web‐building spider fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Indícios de que o fio cribelado tem um custo maior vêm: a) do tempo maior de construção da teia -cerca de 3,5 horas em Uloboridae e cerca de 30 minutos em Araneidae (Lubin, 1986;Zschokke & Vollrath, 1995a,b); b) da construção do fio cribelado com a intensa movimentação das pernas IV (Eberhard, 1988) enquanto o fio viscoso é construído a partir da simples locomoção da aranha pelos raios (Peakall & Witt, 1976); e c) da menor taxa de reciclagem da teia cribelada, quando comparada a Araneidae (Lubin, 1986, Opell, 1998b. Outra medida de custo que poderia ajudar na compreensão de semelhanças e diferenças desses dois tipos de teia orbicular vêm de estudos de metabolismo energético.…”
Section: Tenacidadeunclassified
“…Uma baixa tenacidade, como é esperado para Araneidae devido ao menor custo de construção proporcionado pela composição do fio adesivo (cerca de 80% do volume é composto por água, enquanto todo o fio cribelado é composto inteiramente por proteína - Opell, 1998a), e pela reciclagem diária da teia (araneídeos reciclam sua teia com maior frequência do que uloborídeos -Lubin, 1986;Opell, 1998b) (Higgins, 1995;Janetos, 1986;Lubin et al, 1993;Uetz, 1992;Vollrath, 1985). Não foram usados machos, pois, após a última muda, estes tendem a não construir mais teias e a dispersar à procura das fêmeas.…”
Section: Tenacidadeunclassified
See 1 more Smart Citation